KETAHANAN PANGAN MELALUI DIVERSIFIKASI PANGAN - Leiwakabessy, Ivonne; Manurung, Melani; Penda, Joni; Yanti, Dwi Indah Widya (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Food needs are the most basic needs in determining the quality of human resources. The main aspect of food security is to see local wisdom in traditional agricultural systems. Where it contains knowledge and various strategies in answering various problems related to the environment, meeting food needs, and community adaptation strategies in facing changes in the natural and social environment. Therefore, a strong national food security system is an absolute requirement for successful development by activating public awareness about the importance of diversity of agricultural products in improving family nutrition